A Critical Evaluation of Vitamin D Basic Overview - Gowder, Sivakumar (IntechOpen, 2017)
The book A Critical Evaluation of Vitamin D - Basic Overview targets the physiological, biochemical and immunological aspects of vitamin D, including principles, mechanisms and clinical significance. This book covers four sections: 'Vitamin D on Physical and Physiological Activities', 'Vitamin D on Biochemical and Immunological Activities', 'Vitamin D on Musculoskeletal and Neurological System' and 'Vitamin D on Reproductive System'. Each of these sections is interwoven with the theoretical aspects and experimental techniques of basic and clinical sciences. This book will be a significant source to students, scientists, physicians, healthcare professionals and also other members of this society who are interested in exploring the role of vitamin D in human life. We derive vitamin D from the sunshine, and hence it can also be considered as 'day' vitamin.